Heat stress on sperm quality in dogs: effect of natural antioxidant supplementation - Forte, Lucrezia; Burgio, Matteo; Rizzo, Annalisa; Maggiolino, Aristide; Carbonari, Alice; De Palo, Pasquale; Lacalandra, Giovanni Michele; Cicirelli, Vincenzo (Frontiers in Veterinary Science, 2025)
IntroductionHeat stress negatively affects canine reproductive health by inducing oxidative stress and impairing sperm quality. This study assessed the efficacy of a polyphenolic extract from Loblolly pine (Pinus taeda) lignin (PTHL), in mitigating heat stress-induced oxidative damage and preserving sperm quality in dogs.MethodsForty clinically healthy male dogs were divided into two groups: a control (CON) group receiving a standard diet and a PTHL-supplemented group for 90 days. During summer, dogs were exposed to natural heat stress, and key parameters, including serum biochemical markers, oxidative stress indicators, antioxidant enzyme activity, and sperm quality were evaluated. Mixed-effects models analyzed group, time, and interaction effects.Results and discussionPTHL supplementation significantly reduced plasma TBARS and seminal d-ROMs levels (P < 0.01), indicating lower lipid peroxidation and confirming its protective effects. Antioxidant capacity improved in the PTHL group, with increased activities of antioxidant enzyme activity (SOD, CAT, and GSPx) and elevated plasma Ferric Reducing Antioxidant Power (FRAP) levels (P < 0.01). Notably, the PTHL group demonstrated higher progressive motility (P < 0.01) and a greater percentage of rapid-movement sperm (P < 0.01) at 90 days, indicating improved sperm function under heat stress.ConclusionThese findings suggest that PTHL enhances antioxidant defenses, mitigating heat stress-induced reproductive impairment. This natural strategy may improve fertility in dogs facing environmental challenges. Future studies should explore different dosages and extended supplementation to optimize its benefits.